LITERATURE REVIEW: PERBEDAAN SATURASI OKSIGEN PADA PRIA DAN WANITA AKTIF SECARA FISIK - Fionalita Ratna Rahadi; Asnawati Asnawati; Fauzan Muttaqien; Huldani Huldani; Muhammad Bakhriansyah (Homeostasis, 2022)
Oxygen saturation is an indicator to determine the high and low aerobic capacity. Low oxygen saturation will affect VO2 max, then it will affect the decrease the training strength. High oxygen saturation speeds up the post-workout recovery process. The aim of writing this literature review is to analyze the differences of oxygen saturation in physically active men and women before and after physical activity. This writing was done by literature analysis through a search in medical article’s databese, Google Scholar and PubMed. There are 5 articles in Indonesian and English published in the last 10 years. There is no significant difference of oxygen saturation in men and women before the physical activity. After physical activity, 4 articles show a decrease in oxygen saturation, but 1 article shows a significant increase of oxygen saturation. After physical activity, 4 articles show that the reduction of oxygen saturation in women is less than men, even though there are 2 articles that state the difference by gender is not significant